1970
DOI: 10.1161/01.cir.42.4.719
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Changes Following Correction of Severe Aortic Stenosis Using the Cutter-Smeloff Prosthesis

Abstract: Twelve patients with pure or dominant stenosis were studied before and after aortic valve replacement (Cutter-Smeloff). The changes in cardiac output and A-V O2 difference were small and insignificant, but exercise stroke volume increased from 72 to 96 ml after the surgery. The aortic peak systolic gradient was 92 +/- 29 mm Hg before and 4 +/- 9.8 mm Hg after surgery. The PA wedge pressure, taken as a measure of the LV diastolic pressure, decreased from 18 mm Hg to 12 mm Hg at rest and 30 mm Hg to 16 mm Hg on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

1971
1971
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 13 publications
0
3
1
Order By: Relevance
“…Exclusion of patients with such conditions (or pausing β-blockers) might lead to clearer results with regard to the outcome of AVR, but this may lead to a biased result with regard to the outcome of AVR in patients in the daily practice. The higher age compared with other studies 2 3 18 27 28 in our study group may also affect outcome, but it is a negative indicator of selection, as also expressed by the comparable age distribution in our study and reference groups.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…Exclusion of patients with such conditions (or pausing β-blockers) might lead to clearer results with regard to the outcome of AVR, but this may lead to a biased result with regard to the outcome of AVR in patients in the daily practice. The higher age compared with other studies 2 3 18 27 28 in our study group may also affect outcome, but it is a negative indicator of selection, as also expressed by the comparable age distribution in our study and reference groups.…”
Section: Discussioncontrasting
confidence: 41%
“…The literature on pVO 2 including the change in pVO 2 and predictors of pVO 2 after AVR is sparse. Lee et al 18 found a non-statistically significant mean 12% relative increase in pVO 2 after AVR in 11 severely symptomatic younger patients. 18 Munt et al 2 found no improvement in mean exercise capacity by conventional exercise by testing 34 patients who were initially followed for asymptomatic aortic stenosis and later had AVRs, even though these patients on average improved in resting left ventricular systolic and diastolic function.…”
Section: Discussionmentioning
confidence: 95%
“…9,20 In the early decades of cardiac operations, hemodynamic evaluation of mechanical aortic prostheses was almost impossible. [21][22][23] Surgeons used to evaluate transprosthetic gradients intraoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…In the early seventies, Lee et al reported similar systemic hemodynamic improvements with reduced ventricular preload that closely matched the exercise-induced increase in oxygen consumption in 12 patients, 3 to 6 months following surgical aortic valve replacement. 11 As a maximal cardiopulmonary exercise test was deemed inappropriate and potentially dangerous in elderly patients with severe symptomatic AS, 12 we performed a submaximal bicycle exercise test that was safely conducted in all patients. As it integrates cardiopulmonary and musculoskeletal systems functioning, this test appears suitable for baseline screening, follow-up assessment, and research purposes, particularly among frail subjects.…”
Section: Discussionmentioning
confidence: 99%